Critical Thinking Through Distance Learning: An Analysis of Indonesian Open University - Basidin Mizal; Rayhan Izzati Basith; Tathahira Tathahira (Universitas Teuku Umar, 2021)
This study purposes the enhancement of Critical Thinking ability for students at Indonesian Open University or Universitas Terbuka (UT) and argues that critical thinking can be effectively implemented for online students to improve their skills during their academic life. If it is successful, Indonesian Open University can be better satisfied with their scholars’ quality and sustainable outcomes. This study employed the literature study approach by obtaining the data and information from relevant previous studies. This study suggested that in order to enhance students’ learning outcomes at UT, the instructors are expected to introduce the concept of critical thinking ability through learning content, instructional methods, practice examples and feedback. It is also suggested that students should be encouraged to participate in collaborative learning to stimulate their higher order thinking. The role of instructors and faculty member in designing engaging learning activities and providing accurate information related to learning management system are considerably crucial.